Financial Literacy for Smallholder Livestock Keepers: A Training Manual (Amharic) - Ekule, Muluken; Wamatu, Jane; Goshu, Yehuwanis Goshu; Mengiste, Elsa; Belayneh, Tesfa (International Center for Agricultural Research in the Dry Areas, 2022)
A Training Manual on Financial Literacy for Smallholder Livestock Keepers (Amharic).